2020
DOI: 10.1085/jgp.201912469
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell temperature mapping with fluorescent thermometer nanosheets

Abstract: Recent studies using intracellular thermometers have shown that the temperature inside cultured single cells varies heterogeneously on the order of 1°C. However, the reliability of intracellular thermometry has been challenged both experimentally and theoretically because it is, in principle, exceedingly difficult to exclude the effects of nonthermal factors on the thermometers. To accurately measure cellular temperatures from outside of cells, we developed novel thermometry with fluorescent thermometer nanosh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 46 publications
0
34
0
Order By: Relevance
“…Many articles consider whether temperature gradients can be maintained within single cells 34,35 . The current consensus suggests that significant intracellular gradients are unlikely because heat diffuses too quickly within cells and across membranes 36,37 .…”
Section: Heat Flow and Spatial Scalementioning
confidence: 99%
“…Many articles consider whether temperature gradients can be maintained within single cells 34,35 . The current consensus suggests that significant intracellular gradients are unlikely because heat diffuses too quickly within cells and across membranes 36,37 .…”
Section: Heat Flow and Spatial Scalementioning
confidence: 99%
“…Many articles consider whether temperature gradients can be maintained within single cells (Inada et al, 2019;Suzuki and Plakhotnik, 2020). The current consensus suggests that significant intracellular gradients are unlikely because heat diffuses too quickly within cells and across membranes (Balaban, 2020;Oyama et al, 2020).…”
Section: Heat Flow and Spatial Scalementioning
confidence: 99%
“…Toward this goal, the article from Oyama et al (2020) in this issue of the Journal of General Physiology provides a new method and procedures to monitor the surface temperature of isolated cells avoiding many of the pitfalls of intracellular measurements. These authors used a ratiometric approach on cells grown directly on a fluorescent thermometer nanosheet.…”
mentioning
confidence: 99%
“…This is not always the case for single-cell fluorescent experiments in the literature where optical artifacts have impacted many interpretations over the years. With a properly corrected system, Oyama et al (2020) undertook an impressive set of studies on a wide variety of cell types and protocols previously shown to apparently generate a localized temperature gradient effects inside cells. In agreement with the 10 −5 gap calculations, these authors found no evidence for a large increase in external temperature associated with alterations that should greatly stimulate energy conversion processes in a variety of cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation